Development of sesamin-loaded solid dispersion with α-glycosylated stevia for improving physicochemical and nutraceutical properties. (August 2017) - Sato, Hideyuki; Aoki, Asako; Tabata, Aiko; Kadota, Kazunori; Tozuka, Yuichi; Seto, Yoshiki; Onoue, Satomi
Highlights: Alpha-glycosylated stevia improved the aqueous solubility of sesamin (SES). SES-loaded solid dispersion (SD) system markedly enhanced oral absorption of SES. Orally-dosed SES-loaded SD suppressed drug-induced photodermatosis in rats. Novel SD system might be promising to enhance the nutraceutical potential of SES. Abstract: The present study aimed to enhance the nutraceutical properties of sesamin (SES) by solid dispersion (SD) approach using α-glycosylated stevia (Stevia-G) as a carrier compound with solubilizing effect. The SD formulations were characterized in terms of physicochemical and pharmacokinetic properties. The skin protective effect was evaluated in a rat model of drug-induced photodermatosis. The SES-loaded SD with Stevia-G (SES/Stevia-G-SD) prepared with spray-drying were uniform and spherical with a diameter of about 3 μm, and SES within the formulation was found to be an amorphous state, possibly leading to improved dissolution behavior of SES. SES/Stevia-G-SD provided 190-fold increase in the dissolution amount of SES compared with crystalline SES. The oral bioavailability of SES/Stevia-G-SD (20 mg-SES/kg) was 30-fold higher than that of crystalline SES. Orally-dosed SES/Stevia-G-SD (20 mg-SES/kg) protected rat skins from drug-induced photodermatosis. Based on these findings, the SES/Stevia-G-SD approach might be efficacious to enhance the nutraceutical potential of SES.